2007
DOI: 10.1016/s0929-6646(07)60006-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Improvement Strategy of Analytical Turnaround Time in the Stat Laboratory

Abstract: These findings demonstrated that a dedicated means of process control was able to significantly improve laboratory efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Chien, et al reported that a dedicated process control was able to significantly improve laboratory efficiency [23]. Our lab scientist proceeded to identify factors for improvement after reviewing the study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chien, et al reported that a dedicated process control was able to significantly improve laboratory efficiency [23]. Our lab scientist proceeded to identify factors for improvement after reviewing the study results.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was 90 th percentile test completion from specimen receipt in the lab to the result being reported (In-Lab-TAT90), a better indicator of laboratory performance than mean or median TAT [8, 11]: it captures much of the modifiable outlier effect and represents a standard of consistency required for ED care [23]. Survival analysis was used to determine the In-Lab-TAT90 and 95% confidence interval (CI) for each analyte.…”
Section: Methodsmentioning
confidence: 99%
“…9 According to Tzu-I Chien et al, prioritising the test performance and dedicated means of process control can significantly reduce the TAT of emergency tests without affecting the overall TAT. 10 In a single centre intervention brought about by White BA et al, application of lean methodologies in the form of reallocation of resources without the addition of new resources and simple reorganisation of laboratory process flow effectively decreased the laboratory TAT. 11 Along with customer satisfaction, decreased laboratory TAT also improves the efficiency of ED work by allowing the early diagnosis, treatment, patient discharge and provides a way of cost cutting.…”
Section: Before Intervention After Interventionmentioning
confidence: 99%
“…The CBC analysis performed by large hematology instruments in centralized laboratories today is therefore routinely used to evaluate and monitor bone marrow function in general and specifically in hematological disorders and diseases 4 . However, despite extensive automation, there are inherent challenges in centralizing clinical laboratories (eg, sample logistics and sample processing time) which makes it difficult to achieve turn‐around times (TATs), from requisition/arrival of the patient to availability of results, in less than 30 minutes to 2 hours 5‐7 . A way of overcoming these challenges and achieving TAT <10 minutes is to decentralize the CBC analyses using point‐of‐care (POC) hematology devices to evaluate white blood cells (WBC), platelet (PLT) counts and hemoglobin (HGB) 8 .…”
Section: Introductionmentioning
confidence: 99%